Surgical therapy of end-stage heart failure: understanding cell-mediated mechanisms interacting with myocardial damage - Ghodsizad, Ali; Loebe, Mathias; Piechaczek, Christoph; Bordel, Viktor; Ungerer, Matthias; Gregoric, Igor; Bruckner, Brian; Noon, George P.; Karck, Matthias; Ruhparwar, Arjang (The international journal of artificial organs, 2011)
Worldwide, cardiovascular disease results in an estimated 14.3 million deaths per year, giving rise to an increased demand for alternative and advanced treatment. Current approaches include medical management, cardiac transplantation, device therapy, and, most recently, stem cell therapy. Research into cell-based therapies has shown this option to be a promising alternative to the conventional methods. In contrast to early trials, modern approaches now attempt to isolate specific stem cells, as well as increase their numbers by means of amplifying in a culture environment. The method of delivery has also been improved to minimize the risk of micro-infarcts and embolization, which were often observed after the use of coronary catheterization. The latest approach entails direct, surgical, transepicardial injection of the stem cell mixture, as well as the use of tissue-engineered meshes consisting of embedded progenitor cells.
Gesehen am 15.11.2023